French Pharmacists’ and Veterinarians’ Ethical Perspectives about the Delivery of Antibiotics for Animals: A Content Analysis of Practitioner Literature - Remy, Denise (Journal of applied animal ethics research, 2019)
Amongst the current, most important, international priorities in public health is the issue of bacterial resistance to antibiotics. This issue is due to the wide misuse and overuse of these drugs, both in human and veterinary medicine. Veterinarians fulfil a very important role as guardians of animal health and as public health actors; if they do not use antimicrobials judiciously, animal health and welfare as well as public health will be severely compromised. Therefore it is of particular importance to study the professional ethos of veterinarians as regards the delivery of antibiotics for animals. In Europe laws and practices regarding the delivery of antimicrobial drugs for animals differ from state to state. In some states, veterinarians are not allowed to sell drugs, they only prescribe, and pharmacists deliver the drugs. In other states, including France, veterinarians are allowed to deliver the drugs they prescribe. In France, veterinarians have thus been accused of conflict of interest; of overprescribing to sell more antibiotics and thus earn more money. Therefore, it appeared particularly accurate to not only study the ethos of veterinarians regarding the delivery of antibiotics to animals, but to also compare this ethos to that of pharmacists. To the authors’ knowledge, such a study has never been carried out in any country. Veterinarians’ and pharmacists’ professional literature was studied and compared using qualitative and quantitative content analysis. A sample of comparable journals was selected for both professions. The study was carried out over a relevant five year period extending from the beginning of 2008 till the end of 2012. All papers dealing with antimicrobial resistances as well as the prescription and delivery of antibiotics for animals were objectively and comprehensively searched and collected using keywords. The selected papers were subsequently independently coded by a multidisciplinary team of coders using conventional, inductive, thematic analysis. The final coding grid was obtained after consensus meetings were held in order to ensure reliability and validity of the data. The results showed that the veterinarians’ professional literature studied reflected a primary concern for ethics whereas the pharmacists’ professional literature primarily focused on marketing. Half of the veterinary continuing education papers dealt with different aspects of ethics; the other half focused on the scientific aspects of antimicrobial resistances. Amongst other papers, more than 30% tackled ethical questions in relation with the delivery of antibiotics for animals. Conversely, in the pharmacists’ literature, half of the continuing education papers concentrated on marketing; the other half described the pharmacology of drugs. Amongst other papers, 60% addressed marketing issues. Ethical questions per se were not approached in the pharmacists’ professional literature studied. In conclusion, veterinary ethos for prescription ethics, good antibiotic use and animal welfare seems to be a feature of the profession. According to this research, the claim that veterinarians are responsible for antibiotic resistances because of conflict of interest is not true.